Environmental protection using structural analysis of ships. (September 2019) - Savin, M; Presura, A; Chirica, I
Abstract: Naval accidents are one of the most common causes of water and coast around pollution and also for the deterioration of the associated ecosystems. In order to reduce the risk of spills of hazardous substances in water one of the methods is to study the behavior of naval structures in the event of collisions. This paper aims to propose a methodology for collision analyze, the case study being a river barge structure with side impact generated by another barge. The structural analysis used the finite element method with an explicit solver and the dynamic load of the side impact collision was applied in form of initial kinetic energy of the striking ship. Standard ship design Rules are compared with an original approach to reveal the advantages and disadvantages of each method. The influence of variation of the different parameters on the obtained results is analyzed, in order to outline an efficient and as accurate as possible methodology, considering the necessary computational effort.